Communication from the executive of the Commonwealth, transmitting two ordinances and accompanying papers (LLMC-digital (Series), 1861)
June 17, 1861 communication from Governor John Letcher transmitting a complaint from the presiding judge of Loudon County requesting that an elected "black republican" not be commissioned to serve on the county bench. Of note, ordinances to deal with these situations was referenced in a subsequent letter, but not attached.